PEMBUATAN MESIN PEMERAS JAHE UNTUK II..{DUSTRI KECIL KOPI JAHE BUBUK - -, Darmono (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
Thevoucherprogramentitled"ManufacturingGingerSqueezerN4achine forSmall PowderGinger-CoffeeIndustries"aimstoincreaseproductivityof the UD.ROSEKURNIAespeciallyinsqueezingbasic materialofgingerasa substanceforPowderGinger-Coffeeand CoconutSugarGinger beingproduoed.Italso wants toknowthesuitablesizeand productivitl'of suchgingersqueezer machine.Thesteps ofthismanufacturing gingerrqueere,machineareplanning,machinemanufacturing,andtrainingfor industry partnelworkcrs.T-he plirnningstepincludes; (1)designingrnachine plandrati.(2)cillculatinpgtheneedrld materials, and(3)calculatingtheimplementationcost. I'hemachine-manufacturingstepincludes:(l)materialcuttingtofit theworkdraft.(2) welding,(3)assembling,(4)electricinstallation. (5)machine performancetest. and(6)paintinlg.The trainingfbr industrypartnerworkersconsistsof:(1)theory,andslteechdelivery,(2)demorrstrationofmachineusing,and(3)machineusingpracticeby theindustrypartnerworkers.Theresultof thevoucherprogramisrealizationof a squeezergingermachineandskill achievementby theindustry partner rvorkersinthemachineoperation. squeezergingermachinewasmadeof right-anglediron liamesizing50x50x5rnm,combinedwithplywood of 3mm and 12mm thick.Themachine size is120cmlength,60cmwidth,and190cmheight. nrovcdbyagasolinemotorpowerHONDAof'4 HPandrotationspeedof 1400RP\{. Thecrushingsystem runsby 2 cylindricaltubes with20cm diameterrotatingintheoppositedircction. Themachineperformanceandproductivity forsqueezinegingerhasspeed of 4 to5 timesfastercomparedwithmanualsqueezingsystem havingbeendone uptill now.